Mechanical‐Bending‐Induced Fluorescence Enhancement in Plastically Flexible Crystals of a GFP Chromophore Analogue. (31st August 2020) - Bhattacharya, Biswajit; Roy, Debjit; Dey, Somnath; Puthuvakkal, Anisha; Bhunia, Surojit; Mondal, Saikat; Chowdhury, Rituparno; Bhattacharya, Manjima; Mandal, Mrinal; Manoj, Kochunnoonny; Mandal, Prasun K.; Reddy, C. Malla
Abstract: Single crystals of optoelectronic materials that respond to external stimuli, such as mechanical, light, or heat, are immensely attractive for next generation smart materials. Here we report single crystals of a green fluorescent protein (GFP) chromophore analogue with irreversible mechanical bending and associated unusual enhancement of the fluorescence, which is attributed to the strained molecular packing in the perturbed region. Soft crystalline materials with such fluorescence intensity modulations occurring in response to mechanical stimuli under ambient pressure conditions will have potential implications for the design of technologically relevant tunable fluorescent materials. Abstract : Crystals of a green fluorescent protein chromophore analogue show enhanced fluorescence emission in a plastically deformed mechanically bent state owing to strained molecular packing.